Synthesis, Characterization, Crystal Structure and Antimalarial Activity of (2E)-2-(1-{4-[(7-chloroquinolin-4-yl)amino]phenyl} ethylidene)hydrazine Carbothioamide - Yonathan de J. Parra; Rosa Elena Ferrer; Julia Bruno-Colmenarez; Jaime Charris; Gricela Lobo; Neira Gamboa de Domínguez; Philip J. Rosenthal; Jiri Gut (Orbital: The Electronic Journal of Chemistry, 2017)
A simple synthesis and study by UV-vis, IR, NMR, ESI-CID-MS2 and X-ray diffraction of ((2E)-2-(1-{4-[(7-chloroquinolin-4-yl)amino]phenyl}ethylidene)hydrazinecarbothioamide is reported. It was tested in vitro against chloroquine-resistant strain (W2) of Plasmodium falciparum, hemozoin (β-hematin) formation and cysteine protease falcipain-2. In general, it was found to possess a proved activity in its inhibitory power on the parasite but less active on the formation of hemozoin (β-hematin) and falcipain-2. Also, the X-ray analysis presented an unexpected electronic density that can be assigned like S(2). This electronic density can be attributed to autocondensation of thiosemicarbazide, generating H2S as a subproduct.DOI: http://dx.doi.org/10.17807/orbital.v9i4.1001